2003
DOI: 10.1105/tpc.011650
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin Biosynthesis and Response during Arabidopsis Seed Germination[W]

Abstract: The hormone-mediated control of plant growth and development involves both synthesis and response. Previous studies have shown that gibberellin (GA) plays an essential role in Arabidopsis seed germination. To learn how GA stimulates seed germination, we performed comprehensive analyses of GA biosynthesis and response using gas chromatography-mass spectrometry and oligonucleotide-based DNA microarray analysis. In addition, spatial correlations between GA biosynthesis and response were assessed by in situ hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

42
739
3
18

Year Published

2006
2006
2008
2008

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 820 publications
(802 citation statements)
references
References 85 publications
42
739
3
18
Order By: Relevance
“…Experiments using GA-deficient seeds (Ogawa et al, 2003) have described temporal transcript abundance changes in GA-deficient mutants seeds stimulated to germinate by GA treatment or in nongerminating waterimbibed controls. Dormancy cycling was studied in the Arabidopsis accession Cvi in a range of dormant and after-ripening states.…”
Section: Of 18 the Arabidopsis Bookmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments using GA-deficient seeds (Ogawa et al, 2003) have described temporal transcript abundance changes in GA-deficient mutants seeds stimulated to germinate by GA treatment or in nongerminating waterimbibed controls. Dormancy cycling was studied in the Arabidopsis accession Cvi in a range of dormant and after-ripening states.…”
Section: Of 18 the Arabidopsis Bookmentioning
confidence: 99%
“…However, its role in the regulation of germination and seedling establishment remained obscure (Kucera et al, 2006). Auxin alone was not generally considered to be important in the control of seed germination but cross-talk between auxin, ABA, GA and ethylene was suggested to both affect germination and seedling establishment (Fu and Harberd, 2003;Ogawa et al, 2003; Chiwocha et al, 2005, Carrera et al, 2008Liu, PP et al, 2007 reviewed by Holdsworth et al, 2008a. Analysis of the expression of the DR5:GUS auxin reporter indicated that auxin accumulates during embryogenesis and is present in the seed following imbibition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…GUS activity was hardly detected in the corresponding tissues of the negative control plants (data not shown). Consistent with the GUS activity levels, the promoter region contains several important elements, such as an amylase-box, CARE, GARE, GCN4-motif, ACGT motif and AACA motif, which are involved in seed-specific and normal embryo-specific expression [24,[28][29][30][31]39]. Quantitative GUS assays showed that the highest expression was in Functional analysis of a GhGlcAT1 promoter 180 npg the anthers, with relatively high expression in the stigmas and styles.…”
Section: Histochemical and Quantitative Analysis Of Gus Activitymentioning
confidence: 91%
“…The amylase-box was required for high expression of the gene in the seeds [24], while the E-box was shown to be bound by bHLH (basic helix-loop-helix) transcription factors and to regulate the seed-specific expression of seed storage protein genes and the expression of genes involved in anthocyanin biosynthesis [25][26][27]. The CARE and GARE boxes were required during seed germination in Arabidopsis and rice [28,29]. In addition, a combination of GCN4, ACGT and AACA motifs was sufficient to confer a detectable level of endosperm expression in rice [30,31].…”
Section: Sequence Characterization Of the Ghglcat1 Promoter Regionmentioning
confidence: 99%